Molecular phylogeny and forms of photosynthesis in tribe Salsoleae (Chenopodiaceae) - Schüßler, Christina (The journal of experimental botany, 2016)
While many C4 lineages have Kranz anatomy around individual veins, Salsoleae have evolved the Salsoloid Kranz anatomy where a continuous dual layer of chlorenchyma cells encloses the vascular and water-storage tissue. With the aim of elucidating the evolution of C4 photosynthesis in Salsoleae, a broadly sampled molecular phylogeny and anatomical survey was conducted, together with biochemical, microscopic, and physiological analyses of selected photosynthetic types. From analyses of photosynthetic phenotypes, a model for evolution of this form of C4 was compared with models for evolution of Kranz anatomy around individual veins. A functionally C3 proto-Kranz phenotype (Proto-Kranz Sympegmoid) and intermediates with a photorespiratory pump (Kranz-like Sympegmoid and Kranz-like Salsoloid types) are considered crucial transitional steps towards C4 development. The molecular phylogeny provides evidence for C3 being the ancestral photosynthetic pathway but there is no phylogenetic evidence for the ancestry of C3-C4 intermediacy with respect to C4 in Salsoleae. Traits considered advantageous in arid conditions, such as annual life form, central sclerenchyma in leaves, and reduction of surface area, evolved repeatedly in Salsoleae. The recurrent evolution of a green stem cortex taking over photosynthesis in C4 clades of Salsoleae concurrent with leaf reduction was probably favoured by the higher productivity of the C4 cycle.